Gambaran Kepatuhan Minum Obat pada Penderita TB Paru di Wilayah Kerja Puskesmas Oenuntono Kabupaten Kupang - Jeki A. Toudenga; Petrus Romeo; Eryc Z. Haba Bunga; Ribka Limbu (Yayasan Literasi Sains Indonesia, 2025)
Pulmonary Tuberculosis (TB) is an infectious disease that is a cause of death and a global health problem. Kupang Regency contributed 476 cases of pulmonary TB. The goal of pulmonary TB treatment is to prevent death, prevent recurrence, cure patients and reduce the rate of transmission. Compliance with taking medication in pulmonary TB patients requires active patient participation in self-care management and cooperation between patients and health workers. This study aims to determine the description of compliance with taking medication in pulmonary TB patients in the work area of the Oenuntono Health Center, Kupang Regency, seen from the education, knowledge and support of the patient's family. This type of research is qualitative research whose data is obtained by in-depth interviews. The informants in this study were divided into 3, namely the main informant, key informant and additional informant, while the subjects of this study were all pulmonary TB patients for the period 2024-2025 who were domiciled in the work area of the Oenuntono Health Center, Kupang Regency. The informants in this study were selected using purposive sampling techniques. The processed data were then analyzed using a thematic analysis. Patient knowledge plays an important role in shaping adherence to TB treatment. In addition, the knowledge of health workers and families also plays a role in patient medication adherence. Patient compliance in taking medication is greatly influenced by support from the closest environment, especially family